Reactivity of 2‐Methyl‐4H‐3, 1‐benzoxazin‐4‐ones and 2‐Methyl‐4H‐pyrido[2, 3‐d][1, 3]oxazin‐4‐one under Microwave Irradiation Conditions. (6th September 2013) - Prousis, Kyriakos C.; Tzani, Andromachi; Avlonitis, Nicolaos; Calogeropoulou, Theodora; Detsi, Anastasia
<x xml:space="preserve">Abstract</x> The reactivity of variably substituted 2‐methyl‐4H‐3, 1‐benzoxazin‐4‐ones and 2‐methyl‐4H‐pyrido[2, 3‐d][1, 3]oxazin‐4‐one towards carbon and oxygen nucleophiles under microwave irradiation conditions was investigated. Optimization of the reaction conditions of oxazinones with carbon nucleophiles led to the synthesis of a series of 4‐hydroxy‐quinolin‐2‐ones and 4‐hydroxy‐1, 8‐naphthyridin‐2‐ones in high yields, whereas reaction with a variety of alcohols proceeded smoothly to the formation of the corresponding N‐acetyl‐anthranilates and nicotinates.